2009
DOI: 10.1007/s00534-009-0043-4
|View full text |Cite
|
Sign up to set email alerts
|

Involvement of osteopontin as a core protein in cholesterol gallstone formation

Abstract: These results suggest that Opn is possibly involved as a core protein in the formation of cholesterol gallstones.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
14
0

Year Published

2010
2010
2016
2016

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 15 publications
(15 citation statements)
references
References 29 publications
1
14
0
Order By: Relevance
“…BECAUSE SEVERAL BILIARY proteins have been detected from human gallbladder bile and determined to be factors affecting cholesterol crystal nucleation, 3–12 the concept that cholesterol gallstone depends on an imbalance of the pro‐nucleation and anti‐nucleation factors has been raised. OPN expression has been detected in human GB, and it might correlatewith gallstone formation, 16,24 In our study, results showed that OPN could inhibit the cholesterol crystal nucleation in MB and human GB in vitro . This anti‐nucleation role showed the dose‐dependent property and OPN played the anti‐nucleation role in physiological concentration.…”
Section: Discussionsupporting
confidence: 49%
See 2 more Smart Citations
“…BECAUSE SEVERAL BILIARY proteins have been detected from human gallbladder bile and determined to be factors affecting cholesterol crystal nucleation, 3–12 the concept that cholesterol gallstone depends on an imbalance of the pro‐nucleation and anti‐nucleation factors has been raised. OPN expression has been detected in human GB, and it might correlatewith gallstone formation, 16,24 In our study, results showed that OPN could inhibit the cholesterol crystal nucleation in MB and human GB in vitro . This anti‐nucleation role showed the dose‐dependent property and OPN played the anti‐nucleation role in physiological concentration.…”
Section: Discussionsupporting
confidence: 49%
“…O.D., optical density. with gallstone formation, 16,24 In our study, results showed that OPN could inhibit the cholesterol crystal nucleation in MB and human GB in vitro. This antinucleation role showed the dose-dependent property and OPN played the anti-nucleation role in physiological concentration.…”
Section: B Ecause Several Biliary Proteins Have Beenmentioning
confidence: 53%
See 1 more Smart Citation
“…It exists as a component of the extracellular matrix and as a soluble cytokine. Osteopontin is shown to be involved in cholesterol and pigment gallstone 48, 49. In addition, we also identified other putative pro‐nucleation proteins including aminopeptidase N, orosomucoid 1, orosomucoid 2 and haptoglobin 1 19.…”
Section: Resultsmentioning
confidence: 81%
“…Furthermore, we found that OPN and integrin αv displayed a similar change at the molecular level. Recently, Ichikawa et al [34] demonstrated that the OPN level varied from sites of calculous gallbladder walls, suggesting that OPN plays a different role in gallstone formation. These findings suggest that the functional and structural changes in gallbladders could affect the secretion of OPN and its contents in gallbladder bile, which may be involved in gallstone formation through different pathways in different stage of gallstone disease.…”
Section: Discussionmentioning
confidence: 99%